2012
DOI: 10.1016/j.cell.2012.10.047
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase SIRT6 Is a Tumor Suppressor that Controls Cancer Metabolism

Abstract: Reprogramming of cellular metabolism is a key event during tumorigenesis. Despite being known for decades (Warburg effect), the molecular mechanisms regulating this switch remained unexplored. Here, we identify SIRT6 as a novel tumor suppressor that regulates aerobic glycolysis in cancer cells. Importantly, loss of SIRT6 leads to tumor formation without activation of known oncogenes, while transformed SIRT6-deficient cells display increased glycolysis and tumor growth, suggesting that SIRT6 plays a role in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
613
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 580 publications
(655 citation statements)
references
References 58 publications
24
613
3
4
Order By: Relevance
“…These enzymes act as deacetylases, desuccinylases and demalonylases, and at least two members of the Sirtuin family, SirT5 and SirT6, have been implicated in GLS regulation. Sebastian et al showed that SirT6 represses MYC, and, by extension, the expression of GLS [112]. A more direct interaction was demonstrated by Poletta and colleagues, who used immunoprecipitation assays to show that GLS binds directly to SirT5 [113].…”
mentioning
confidence: 89%
“…These enzymes act as deacetylases, desuccinylases and demalonylases, and at least two members of the Sirtuin family, SirT5 and SirT6, have been implicated in GLS regulation. Sebastian et al showed that SirT6 represses MYC, and, by extension, the expression of GLS [112]. A more direct interaction was demonstrated by Poletta and colleagues, who used immunoprecipitation assays to show that GLS binds directly to SirT5 [113].…”
mentioning
confidence: 89%
“…Mechanistically, SIRT6 suppresses aerobic glycolysis and Mycdependent ribosome biosynthesis, and lack of this sirtuin leads to robust metabolic reprogramming, sufficient to promote tumorigenesis. In line with this, Sirt6 expression is down-regulated in human pancreatic and colorectal cancers, and conditional deletion of Sirt6 promotes intestinal tumorigenesis in vivo (106). Consistent with a tumor-suppressive function, it has recently been shown that overexpression of SIRT6 induces apoptosis in cancer cell lines (55).…”
Section: Cancermentioning
confidence: 59%
“…As noted above, SIRT6 is a key regulator of glucose metabolism, and lack of this chromatin factor leads to a phenotype that is reminiscent of the Warburg effect (37). Indeed, SIRT6 has been recently described as a tumor suppressor that regulates cancer metabolism (106). Mechanistically, SIRT6 suppresses aerobic glycolysis and Mycdependent ribosome biosynthesis, and lack of this sirtuin leads to robust metabolic reprogramming, sufficient to promote tumorigenesis.…”
Section: Cancermentioning
confidence: 99%
“…SIRT6-deficient mice have a striking degenerative phenotype leading to shortened lifespan and are associated with hypoglycemia and defects in DNA repair (2). Deletion of SIRT6 is sufficient to promote tumorigenesis independent of oncogene activation (3). SIRT6 overexpression lowers LDL and triglyceride levels, improves glucose tolerance (4), and increases lifespan of male mice (5).…”
mentioning
confidence: 99%